Identifying lines of the black-eyed cowpea having high productivity and quality commercial grain - Delmondes, Bruna; Menezes Júnior, José Ângelo; Silva, Kaesel Jackson; Rocha, Maurisrael; Neves, Adão; Pereira, Cassiano (Revista Ciência Agronômica, 2017)
The black-eyed cowpea, is consumed in Brazil and valued in various other countries, and for this reason, can be found on the domestic market, showing the potential for export. The aim of this study was to identify lines of the black-eyed cowpea having high productivity and quality commercial grain. Twenty-four lines of black-eyed commercial subclass of cowpea, taken from the breeding program of Embrapa Meio-Norte, and two controls (BRS Itaim and CB-27) were evaluated. The experiments were carried out in Nova Ubiratã, in the State of Mato Grosso, Brazil (MT) during 2014, and in Primavera do Leste MT and Sinop MT during 2015, in the off-season; planting was in February/March and harvesting in May/June. The experimental design was of randomised complete blocks with four replications, in plots of 4 rows of 5 metres spaced 0.45 metres apart. Crop value, lodging and grain productivity were evaluated. The occurrence of blemished grain was also assessed, both by counting the blemished grain (visual selection), and by colorimetric analysis, using the CIE L* a* b* colour scale. Four lines showed potential for inclusion in the trials for crop value and use (VCU) as per the recommendation of the State of Mato Grosso, by combining grain productivity comparable to that of the BRS Itaim cultivar and a low percentage of blemished grain. Visual evaluation by counting the blemished grain, was efficient in identifying lines of the black-eyed cowpea with better grain quality in relation to the BRS Itaim cultivar. Colour reading using the CIE L* a* b* scale did not satisfactorily differentiate the occurrence of blemished grain in lines of the black-eyed cowpea.